2022
DOI: 10.1039/d1sc07044d
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric [3 + 2] photocycloadditions of cyclopropylamines with electron-rich and electron-neutral olefins

Abstract: Radical addition to olefins is a common and useful chemical transformation. In the context of offering enantioenriched three-dimensional molecules via such a highly reactive process, chiral hydrogen-bonding (H-bonding) catalysis has...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…More recently, they managed to extend the scope to electron-rich and electronneutral olefins by developing a remote H-bonding induction strategy (Scheme 15B). 58 After extensive catalyst screening, a SPINOL-based chiral phosphoric acid (CPA) was found to be the optimal catalyst for this reaction. Various types of olefins, such as 3-methylene-isoindolin-1-one (38), a-phenyl ethenamine (39) and 1,1-diarylethylene (40), are well tolerated in this catalytic system although reaction conditions need to be optimized in each case.…”
Section: Asymmetric (3+2) Annulations With Alkenesmentioning
confidence: 99%
“…More recently, they managed to extend the scope to electron-rich and electronneutral olefins by developing a remote H-bonding induction strategy (Scheme 15B). 58 After extensive catalyst screening, a SPINOL-based chiral phosphoric acid (CPA) was found to be the optimal catalyst for this reaction. Various types of olefins, such as 3-methylene-isoindolin-1-one (38), a-phenyl ethenamine (39) and 1,1-diarylethylene (40), are well tolerated in this catalytic system although reaction conditions need to be optimized in each case.…”
Section: Asymmetric (3+2) Annulations With Alkenesmentioning
confidence: 99%
“…The stereodetermining step is depicted in Scheme . Recently, the scope of this methodology was extended to electron-rich and electron-neutral olefins . A related, Lewis-acid-catalyzed reaction was published the same year .…”
Section: Reactions Based On Anion Bindingmentioning
confidence: 99%
“…52 Recently, the scope of this methodology was extended to electron-rich and electron-neutral olefins. 53 A related, Lewis-acid-catalyzed reaction was published the same year. 54 Taken together, this particular photoredox-mediated [3 + 2] cycloaddition of cyclopropyl amine derivatives to olefines shows how one synthetic challenge can be addressed by three different modes of asymmetric catalysis depending of the substrate's structure and its interaction with the respective catalytic system.…”
Section: ■ Reactions Based On Anion Bindingmentioning
confidence: 99%
“…Zhao, Cao, Jiang, and co-workers have since reported an analogous approach using a chiral phosphoric acid catalyst. [21] Fraile and Aleman showed that chirality at a Rh photocatalyst's metal center can also lead to asymmetric (3 + 2)-CA of cyclopropylanilines with bidentate, imidazole-containing enones, though the alkene scope is limited by the transient chelation requirement (Figure 6). [22] Though electron transfer occurs in the outer sphere, the enantiodetermining radical addition occurs near the metal.…”
Section: Nitrogen: Anilinesmentioning
confidence: 99%
“…Ideally, only this catalyst‐bound material undergoes the downstream enantiodetermining cyclization step, the facial selectivity of which is controlled by H‐bonds with the catalyst. Zhao, Cao, Jiang, and co‐workers have since reported an analogous approach using a chiral phosphoric acid catalyst [21] …”
Section: The β‐Scission Approachmentioning
confidence: 99%